Hindpaw Withdrawal from a Painful Thermal Stimulus after Sciatic Nerve Compression and Decompression in the Diabetic Rat - Barac, Sorin; Jiga, Lucian P.; Barac, Beatrice; Hoinoiu, Teodora; Dellon, A. Lee; Ionac, Mihai (Journal of Reconstructive Microsurgery, 2013)
Introduction Although the effect of chronic compression and surgical decompression of the diabetic rat sciatic nerve has been evaluated by walking track analysis, the measurement of sensory function by response to thermal nociceptive stimulation has not been investigated.Methods Fifteen male Wistar rats with streptozotocin-induced diabetes underwent sciatic nerve compression through a 10-mm silicone band. Five rats had histology done 60 days after confirming chronic nerve compression. Pain threshold was measured using hindlimb withdrawal times (HLWT) from a heat stimulus. After 60 days of compression, the silicone tube was removed. Five nondiabetic, nonbanded rats were used as controls.Results Control mean HLWT was 9.7 ± 1.5 sec. In the diabetes group (60 days of compression), mean HLWT was 23.6 ± 2.4 sec. (p < 0.001). Thirty days after removal of the silicone, mean HLWT to painful stimuli was 14.9 ± 1.5 sec. (p < 0.001).Conclusion Chronic compression of the diabetic rat sciatic nerve increases (worsens) the threshold to heat (pain) perception. Decompression reverses this effect (improves nociception).
Keywords: diabetes; pain; nerve compression